FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURRAHMAN SALEH SITUBONDO DENGAN MINAT INVESTASI SEBAGAI VARIABEL INTERVENING - Utami, Marisa Tri; Hamdun, Edy Kusnadi; Wiryaningtyas, Dwi Perwitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The research objective is to determine the factors that influence investment decisions in students of the Faculty of Economics and Business, University of Abdurachman Saleh Situbondo with interest in investment as an intervening variable. The sampling technique used in this study was proportional stratified random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that investment knowledge has a significant effect on interest, technological progress has a positive and significant effect on invesment interest, investment knowledge has a negative and insignificant effect on investment decisions, technological progress has a positive and significant effect on investment decisions,invesment interest has a positive and significant effect on investment decisions, investment knowledge has a positive and significant effect on investment decisions through interest in technological progress has a positive and significant effect on investment decisions through invesment interest.